Removal of mobile genetic elements from the genome of Clostridioides difficile and the implications for the organism’s biology - Hussain, Haitham; Nubgan, Amer; Rodríguez, César; Imwattana, Korakrit; Knight, Daniel R.; Parthala, Valerija; Mullany, Peter; Goh, Shan (Frontiers in Microbiology, 2024)
Clostridioides difficile is an emerging pathogen of One Health significance. Its highly variable genome contains mobile genetic elements (MGEs) such as transposons and prophages that influence its biology. Systematic deletion of each genetic element is required to determine their precise role in C. difficile biology and contribution to the wider mobilome. Here, Tn5397 (21 kb) and f027 (56 kb) were deleted from C. difficile 630 and R20291, respectively, using allele replacement facilitated by CRISPR-Cas9. The 630 Tn5397 deletant transferred PaLoc at the same frequency (1 x 10 -7 ) as 630 harboring Tn5397, indicating that Tn5397 alone did not mediate conjugative transfer of PaLoc. The R20291 f027 deletant contained two unexpected features, a 2.7 kb remnant of the mutagenesis plasmid, and a putative catalase gene adjacent to the deleted prophage was also deleted. Growth kinetics of R20291 f027 deletant was similar to wild type (WT) in rich medium but marginally reduced compared with WT in minimal medium. This work indicates the commonly used pMTL8000 plasmid series works well for CRISPR-Cas9-mediated gene deletion, resulting in the largest deleted locus (56.8 kb) described in C. difficile. Removal of MGEs was achieved by targeting conjugative/integrative regions to promote excision and permanent loss. The deletants created will be useful strains for investigating Tn5397 or f027 prophage contribution to host virulence, fitness, and physiology, and a platform for other mutagenesis studies aimed at functional gene analysis without native transposon or phage interference in C. difficile 630 and R20291.